Diagnostic performance of detecting breast cancer on computed radiographic (CR) mammograms: comparison of hard copy film, 3-megapixel liquid-crystal-display (LCD) monitor and 5-megapixel LCD monitor. - Yamada T; Suzuki A; Uchiyama N; Ohuchi N; Takahashi S; Yamada, Takayuki; Suzuki, Akihiko; Uchiyama, Nachiko; Ohuchi, Noriaki; Takahashi, Shoki (European Radiology, 2008)
The purpose was to compare observer performance in the detection of breast cancer using hard-copy film, and 3-megapixel (3-MP) and 5-megapixel (5-MP) liquid crystal display (LCD) monitors in a simulated screening setting. We amassed 100 sample sets, including 32 patients with surgically proven breast cancer (masses present, N = 12; microcalcifications, N = 10; other types, N = 10) and 68 normal controls. All the mammograms were obtained using computed radiography (CR; sampling pitch of 50 mum). Twelve mammographers independently assessed CR mammograms presented in random order for hard-copy and soft-copy reading at minimal 4-week intervals. Observers rated the images on seven-point (1 to 7) and continuous (0 to 100) malignancy scales. Receiver-operating-characteristics analysis was performed, and the average area under the curve (AUC) was calculated for each modality. The jackknife method with the Bonferroni correction was applied to multireader/multicase analysis. The average AUC values for the 3-MP LCD, 5-MP LCD, and hard-copy film were 0.954, 0.947, and 0.956 on the seven-point scale and 0.943, 0.923, and 0.944 on the continuous scale, respectively. There were no significant differences among the three modalities on either scale. Soft-copy reading using 3-MP and 5-MP LCDs is comparable to hard-copy reading for detecting breast cancer.